2020
DOI: 10.3390/jrfm13100236
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Resilience of the Austrian Agriculture since the EU Accession

Abstract: Ensuring sustainable and economically viable agriculture requires economic resilience before, throughout, and after a shock. This paper studies the economic resilience of Austrian agriculture within the period of 1995 to 2019. However, methods for tracking changes in economic resilience have so far seen only limited application in agriculture. The index for the analysis and measurement of economic resilience is based on four areas: financial flexibility, stability in following the development path, diversifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 90 publications
0
13
0
4
Order By: Relevance
“…This study preliminarily defined the concept of CLSR and emphasized the adaptability of cultivated land systems to create a new path of transformation on the basis of previous studies on cultivated land use transformation; it also evaluated the future development capacity of cultivated land systems. Compared to other similar studies [50,63], the innovation here lies in the establishment of an empirical research framework of theoretical analysis-index evaluation factor detection and governance countermeasures from the aspects of constructing all aspects of CLSR indicators and provincial-scale comparison and regional classification and grading, which complements CLSR research system and is part of socio-ecosystem resilience research. Similar to previous studies, we all believe that resilience emphasizes adaptive learning and transformation ability, which is an important supplement to sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study preliminarily defined the concept of CLSR and emphasized the adaptability of cultivated land systems to create a new path of transformation on the basis of previous studies on cultivated land use transformation; it also evaluated the future development capacity of cultivated land systems. Compared to other similar studies [50,63], the innovation here lies in the establishment of an empirical research framework of theoretical analysis-index evaluation factor detection and governance countermeasures from the aspects of constructing all aspects of CLSR indicators and provincial-scale comparison and regional classification and grading, which complements CLSR research system and is part of socio-ecosystem resilience research. Similar to previous studies, we all believe that resilience emphasizes adaptive learning and transformation ability, which is an important supplement to sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…In the framework of the social ecosystem, understanding the interactions between farm change characteristics and the social natural system, and cultivating the ability of farm systems to renew and reorganize themselves in the face of external disturbances is an important part of realizing the sustainable development of farms [49]. Farms face disturbances from conflict, natural disasters, climate change, demand for food, price fluctuations, and health crises [50]; its resilience can be improved by the number of farm facilities, farmers' age, agricultural terms of trade, agricultural output, and other aspects [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Such an applied approach provides clear directions to decision makers where to direct Governmental measures aimed at increasing countries economic resilience of agriculture. This paper contributes Morkūnas, Volkov and Pazienza (2018), Michel-Villarreal et al (2019), Quendler and Morkūnas (2020), Hassani and Fantke (2020) [23][24][25][26] insights enriching it with more applied perspective on a meso-economic level. The scientific novelty of the proposed methodology relies on the aggregate-level approach towards resilience of agriculture.…”
Section: Introductionmentioning
confidence: 93%
“…The analysis showed that economic diversification is a strategy to increase agricultural productivity and mitigate the adverse impact of droughts and floods on agricultural households. Next, the authors of [42] examined the economic resilience of Austrian agriculture during the period 1995-2019, by considering a selection of indicators of financial flexibility, stability in following the development path, diversification of activities, and diversification of export markets, and found that the agricultural sector in the country is quite resilient and forgiving of shocks. Finally, the authors of [9] studied the Lithuanian agricultural resilience within a threedimensional context consisting of the production of food at affordable prices, assurance of farm viability, and provision of employment opportunities with a decent income for agricultural workers, on data from the period 2012-2019.…”
Section:   mentioning
confidence: 99%